Bioanalytical LC separation techniques for quantitative analysis of free amino acids in human plasma. (February 2013) - Meesters, Roland JW
The quantitative analysis of free amino acids in human plasma has become an important and essential analysis parameter in different areas of life sciences. Free amino acid concentrations in human plasma samples are generally determined by means of GC or LC after chemical derivatization followed by UV, fluorescent or MS detection of the amino acid derivatives. Derivatization of free amino acids is done either pre- or post-column, and the amino acid derivatives obtained posess improved chromatographic behavior, increased detection sensitivity and selectivity compared with non-derivatized free amino acids. This work gives an overview of different chemical derivatization methods applied and their liquid separation techniques in bioanalytical assays for quantitative free amino acid analysis in human plasma samples. Important plasma preparation procedures, pre- and post-column derivatization, and different LC separation techniques are presented.